Artificial Intelligence Adoption and Business Sustainability in Sharia MSMEs: The Mediating Role of Entrepreneurial Orientation - M Alfisyahrin (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2026)
This study investigates the role of entrepreneurial orientation as a mediating variable in the relationship between artificial intelligence (AI) adoption and business sustainability in Sharia-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, The degree of digital maturity moderates the influence of AI on firm sustainability.. Adopting a quantitative approach using Structural Equation Modeling (SEM), data were collected from 212 Sharia MSMEs that have integrated digital-based fintech or AI systems into their operations. The findings indicate that AI adoption significantly improves OK and business sustainability, while OK partially mediates this relationship. Furthermore, TD positively moderates the effect of AI adoption on sustainability outcomes. These results confirm that integrating behavioral and digital dimensions into a maqashid-oriented entrepreneurship framework strengthens ethical and sustainable business practices. Theoretically, this study contributes by expanding the Resource-Based View (RBV) and behavioral entrepreneurship theory into the Islamic context. Practical implications are presented for policymakers, Islamic financial institutions, and MSME actors to encourage AI adoption that is in line with Islamic ethics and maqashid al-shariah principles.